2020
DOI: 10.1007/s10668-020-01004-5
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus disease-19 in environmental fields: a bibliometric and visualization mapping analysis

Abstract: A coronavirus disease-19 (COVID-19) caused by a novel coronavirus has appeared in China by the end of 2019 and later recognized as a global pandemic. This pandemic has evolved as a global public health menace. It has affected every aspect of human life. In line with these concerns, governments and the scientific community react promptly to the outbreak of this pandemic. These efforts are devoted to develop vaccine and curative medicines. Further efforts are dedicated to assessing the impacts of the pandemic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 70 publications
0
41
0
1
Order By: Relevance
“…The disease is caused by SARS CoV-2, which connotes a severe acute respiratory syndrome coronavirus-2 (Zhai et al, 2020). The World Health Organisation gave the virus the name Covid-19, while the international committee coined SARS CoV-2 on the taxonomy of viruses (ICTV) (Zyoud and Zyoud, 2020). Worldometer (2020) revealed that over 68 million people had been infected, resulting in the death of over 2 million people worldwide.…”
Section: Nature and Symptoms Of Covid-19mentioning
confidence: 99%
“…The disease is caused by SARS CoV-2, which connotes a severe acute respiratory syndrome coronavirus-2 (Zhai et al, 2020). The World Health Organisation gave the virus the name Covid-19, while the international committee coined SARS CoV-2 on the taxonomy of viruses (ICTV) (Zyoud and Zyoud, 2020). Worldometer (2020) revealed that over 68 million people had been infected, resulting in the death of over 2 million people worldwide.…”
Section: Nature and Symptoms Of Covid-19mentioning
confidence: 99%
“…A bibliometric analysis of publications during this period is, therefore, necessary, allowing us to organize large volumes of information, assess the current status of a certain research domain and help to provide directions or ideas for future research ( Alessandro et al, 2019 , Han et al, 2019 ). However, the previously published bibliometric articles on COVID-19 have mostly investigated research activity in environmental fields ( Zyoud and Zyoud, 2020 ), business management fields ( Verma and Gustafsson, 2020 ), and biomedical research areas ( Deng et al, 2020 , Francesca and Antonella, 2020 , Tao et al, 2020 ). A bibliometric analysis of the psychiatry and psychology field is still needed.…”
Section: Introductionmentioning
confidence: 99%
“…To date, there is not a bibliometric study assessing depression research and COVID-19 at the global level. In several studies in virology[ 17 - 22 ], more specifically on the COVID-19 outbreak[ 23 - 29 ], bibliometric analysis means evaluating the research output of authors, countries, journals, and institutions[ 30 , 31 ]. Capturing the relevant literature is essential and promotes the comprehension of a particular focus area's characteristics and patterns.…”
Section: Introductionmentioning
confidence: 99%